A Comparative Study of Electrocautery Versus Cold Scalpel For Skin Incision In Inguinal Hernia Repair - Ansari, Meraj Alam; Mishra, S. M.; Baskota, B. D. (Journal of Nepalgunj Medical College, 2017)
Introduction: Electrocautery has been widely used except for the skin incisions; this is because of the fear of scarring of skin, post operative pain, poor wound healing and wound infection in view of devitalisation of tissues. Although still not very popular, yet the use of diathermy instead of scalpel for making skin incision and underlying tissue dissection is gradually gaining wide acceptance. The purpose of this study was to compare the scalpel incision with electrocautery incision over skin in patients undergoing hernia repair.Aims and Objectives: To compare the skin wound made by the diathermy and scalpel with a view in; intraoperative incision time, post operative pain, requirement of analgesia and the quality of wound healing.Material and Methods: This is hospital based comparative study, undergone elective inguinal hernia repair in the department of general surgery at Nepalgunj medical college teaching hospital, Kohalpur from the period of July 2015 to January 2016. Group A, contained 30 patients who underwent skin incision with scalpel and Group B, also contained 30 patients who underwent skin incision with electrocautery. These groups were compared and statistical analysis using SPSS (version 20) was done and p value 0.05 was taken as significant.Results: Compared with a scalpel incision, cutting diathermy resulted in significantly shorter incision time (p